Application of Nano-Titanium Dioxide to Collapsible Gypseous Soils for Stabilization - Jassim, Najwa Wasif; Mastura Azmi; Mohammed Yousif Fattah (Journal of Engineering and Sustainable Development, 2026)
Nano titanium dioxide is a soil chemical additive that can act as a cementing agent and water barrier. This research aims to investigate how different percentages of NTD affect the collapsibility and severity of natural sandy soils with gypsum contents of 35, 50, and 60%, taken from three other locations in the Salah Al-Deen government. Single- and double-oedometer tests were conducted to investigate the collapsibility of gypseous soils stabilized with NTD and to compare them with untreated soil samples. All test results for both single- and double-oedometer tests showed a significant effect of NTD on decreasing Cp values, with varying percentages and, hence, a transformation in the degree of severity across the three tested soils at NTD percentages of 0.1, 0.3, and 0.5%. These findings suggest that even trace amounts of NTD could be a promising agent for stabilizing collapsible gypseous soils in civil engineering projects. This could lead to more stable and reliable ground support in areas with prevalent soil types. Advances in the application of nano titanium dioxide are opening new avenues for enhancing soil stabilization techniques and ensuring the longevity of engineering structures.